Alternative Tourism Attraction Policy of Makassar City - Islahuddin Islahuddin; Rani Dian Aryani Rajid; Aris Baharuddin (Program Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to examine the creation of alternative tourism attractions in Makassar City. It is qualitative research, and the informants include the Mayor of Makassar, the Head of the Department of Tourism and Creative Economy, the Head of the Makassar District, the Chairman of the Regional Board of the Indonesian Hotel and Restaurant Association (PHRI) in South Sulawesi, the Chairman of the Regional Board of the Association of Indonesian Tours and Travel Agencies (ASITA) in South Sulawesi, and the local community. Data was collected through observation, interviews, and documentation. The data analysis technique employed was qualitative descriptive analysis, involving data reduction, data presentation, and conclusion drawing or verification. The research findings indicate that the implementation of the Makassar Tidak Rantasa (MTR) Policy, which includes the Lorong Garden program, has successfully transformed several alleys or lanes into cleaner, healthier, and more attractive places to visit, particularly in the Makassar District. However, these changes have not yet created alternative tourism attractions. The recommendation from this study emphasizes the need to consider the principles of tourism attraction management to follow up on the Lorong Garden program and ultimately create alternative tourism attractions in Makassar City.